2014
DOI: 10.1021/es404679y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically Enhanced Degradation of Pyrene and Phenanthrene Loaded on Magnetite

Abstract: The enhancement of the degradation of polycyclic aromatic hydrocarbons (PAHs), exemplified by pyrene and phenanthrene, using mild grinding in the presence of common minerals was investigated. Magnetite, birnessite, and Na- and Cu-montmorillonite samples were loaded with pyrene or phenanthrene and ground manually or in a ball mill for short periods of time. The ground samples were analyzed for PAHs and for their metabolites, using high-performance liquid chromatography and liquid chromatography-mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…It is also possible that the "magnetite" grinding may generate new Fe III -sites, which would be responsible for PAH oxidation as claimed by the authors. 1 If the latter was the sole mechanism, similar results should be obtained with Fe III -oxides like maghemite or hematite. Without this type of data, the specific contribution of magnetite as a Fe II −Fe III mixed valence oxide in the observed oxidation of PAH cannot be evidenced.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…It is also possible that the "magnetite" grinding may generate new Fe III -sites, which would be responsible for PAH oxidation as claimed by the authors. 1 If the latter was the sole mechanism, similar results should be obtained with Fe III -oxides like maghemite or hematite. Without this type of data, the specific contribution of magnetite as a Fe II −Fe III mixed valence oxide in the observed oxidation of PAH cannot be evidenced.…”
mentioning
confidence: 63%
“…It is worthwhile to note that the mechanochemical degradation of pyrene was observed here 1 only with divalentcation bearing minerals (i.e., Cu-mont and magnetite), and not with the Mn VI −Mn III -oxide (i.e., birnessite) that is usually shown to induce this type of degradation, as reported in numerous works cited by the authors. 1 Third, the authors found that the water addition to the PAHspiked soil/magnetite mixture followed by drying before milling resulted in 10−16% of PAH degradation. This has been attributed by the authors to desorption of PAH from soil components, following by a diffusion of molecules to reach the added magnetite surface.…”
mentioning
confidence: 99%
See 3 more Smart Citations